Prognostic factors that increase the risk for reduced white matter volumes and deficits in attention and learning for survivors of childhood cancers. Issue 6 (25th January 2014) - Reddick, Wilburn E.; Taghipour, Delaram J.; Glass, John O.; Ashford, Jason; Xiong, Xiaoping; Wu, Shengjie; Bonner, Melanie; Khan, Raja B.; Conklin, Heather M.
Abstract Objective In children, CNS‐directed cancer therapy is thought to result in decreased cerebral white matter volumes (WMV) and subsequent neurocognitive deficits. This study was designed as a prospective validation of the purported reduction in WMV, associated influential factors, and its relationship to neurocognitive deficits in a very large cohort of both acute lymphoblastic leukemia (ALL) and malignant brain tumors (BT) survivors in comparison to an age similar cohort of healthy sibling controls. Procedures The effects of host characteristics and CNS treatment intensity on WMV were investigated in 383 childhood cancer survivors (199 ALL, 184 BT) at least 12 months post‐completion of therapy and 67 healthy siblings that served as a control group. t‐Tests and multiple variable linear models were used to assess cross‐sectional WMV and its relation with neurocognitive function. Results BT survivors had lower WMV than ALL survivors, who had less than the control group. Increased CNS treatment intensity, younger age at treatment, and greater time since treatment were significantly associated with lower WMV. Additionally, cancer survivors did not perform as well as the control group on neurocognitive measures of intelligence, attention, and academic achievement. Reduced WMV had a larger impact on estimated IQ among females and children treated at a younger age. Conclusions Survivors of childhood cancer that have undergone higher intensity therapy at a younger age have significantly less WMV than their peers and this difference increases with time since therapy. Decreased WMV is associated with significantly lower scores in intelligence, attention, and academic performance in survivors. Pediatr Blood Cancer 2014;61:1074–1079. © 2014 Wiley Periodicals, Inc.